Adaptation and destabilization of interpersonal relationships in sport and music during the Covid-19 lockdown - Antonini Philippe, R.; Schiavio, A.; Biasutti, M. (Heliyon, 2020)
The 2020 COVID-19 pandemic and the resulting imposition of physical distancing rules had consequences in the domains of music and sport. The present study sought to analyze how the COVID-19 lockdown period affected interpersonal relationships between music teachers and students and sports coaches and athletes. As part of a semi-structured interview, eighteen participants—six athletes and their three coaches and six musicians and their three teachers—were asked to recall how their interpersonal relationships evolved during the lockdown. Findings showed that these changes could be grouped into four dimensions: establishing a new relationship; working on a new form for the relationship; developing functional, positive adaptations; and developing non-adaptive, detached relationships. Findings also showed that members of the dyad gave meaning to their interpersonal relationship in a dynamic way, even over such a short time. There were some similarities between the experiences of musicians and athletes, highlighting the importance of a well-functioning dyad and good communication between the parties.